Towards Islamicising technology development : A 'Shaping' perspective - Saidin, Aznan Zuhid; Muhammad, Amran (2013)
Technology is seen as having features that 'empowers' as well as affects man. However, man's relation with the technology that is developed based on their scientific knowledge should be that of a master, rather than as a victim that succumbs to the effects of technology. The deterministic position of technology has been debunked by Western scholars, putting forward the influence of social context as the force that shapes technology. This can be seen in the various perspectives proposed by them such as the social construction of technology (SCOT), systems approach, actor-network theory, neo-Marxist approach and consumption approach. In this light, a similar perspective is considered in suggesting an approach towards Islamicising technology development. This Islamic shaping of technology by Muslims has the aim of producing technologies that will bring one to the recognition of Allah as the All Powerful Being and Sole Creator, i.e. placing Tawḥīd as the foundation of developing technology. Apart from this, the technology that is developed also addresses the needs of mankind guided by the higher intents of the shariah or the Maqāṣid al-Sharī'ah. It is hoped that with this approach, technology is created and used not for bringing about a life of confusion and destruction but for attaining a harmonious life with the Creator.